Edukasi DAGUSIBU dan pemusnahan obat di SMA Unggulan BPPT Zainul Hasan Probolinggo - Azis, Fahmi Dimas Abdul; Lukman, Hilmia; Anggara, Suwandre Dwi; Khalishah, Nur (P3HKI - Universitas Muhammadiyah Parepare, 2024)
Education regarding DAGUSIBU and how to destroy drugs at SMA Unggulan BPPT Zainul Hasan Genggong. Indonesian people are now getting used to the use of various types of medicines. Among teenagers, most of them consume drugs without knowing how to use and handle drugs properly and correctly, such as how to get drugs, use drugs, store drugs and dispose of drugs. The aim of DAGUSIBU drug education is one of the efforts that can be made as a pharmaceutical worker to prevent irrational use of drugs and ensure that there is no protection of drugs by the public. The method used, namely collaborating with SMA Unggulan BPPT Zainul Hasan Genggong to provide education in the form of interactive seminars with a visual approach, so that students are explained about obtaining, using, storing and disposing of medicines. The indicator of success of this activity is increasing the knowledge of BPPT Zainul Hasan Genggong High School students about obtaining, using, storing and disposing of medicines. Apart from that, students are expected to become agents of change in their families and surrounding communities by spreading the knowledge they have acquired.